Cultural adaptation of a digital therapeutic for insomnia for Spanish-speaking Hispanic adults in the United States: a qualitative studyResearch in context - Carmela Alcántara; Luciana Giorgio Cosenzo; Sarah V. Diaz; Darwin Arias; Joseph E. Schwartz; Ian M. Kronish; Nathalie Moise (The Lancet Regional Health. Americas, 2025)
Summary: Background: Digital therapeutics represent an innovative and scalable means for addressing inequities in access to behavioural healthcare. However, the adaptation of digital health technologies for minoritised communities to promote equitable uptake remains elusive, and the procedures and outcomes are often not systematically detailed. Our aim was to describe the equity-centred, theory-informed process we undertook to culturally adapt, for Spanish-speaking Hispanic adults, the first Food and Drug Administration authorized, self-guided, prescription digital therapeutic for insomnia. Methods: We used an integrated four-stage model of cultural adaptation to guide the process and a cultural adaptation taxonomy of common elements to report findings. A bilingual (Spanish/English) community advisory board provided critical input. In Stages 1–3, ten focus groups and 13 individual interviews were conducted to obtain feedback on cultural adaptations and digital components. In Stage 4, a pilot study was undertaken to assess usability of the adaptations. Qualitative data were analysed using thematic content analysis and coded by type of adaptation. Findings: 53 Hispanic adults with chronic insomnia were invited to participate in all stages; Mean age = 53.6 years (SD = 11.4), 64.2% women, 49% less than college, and 62.3% reported low technological confidence. Cultural adaptations were made in each taxonomy component (83 total); the adapted program had high usability (System Usability Scale = 95/100). Surface-level adaptations (34.9% of changes made based on observable characteristics), which included changes to the characters (storylines, images), activities, and content to reflect the within-Hispanic group heterogeneity. Deep-level adaptations (65.1% of changes made based on sociocultural factors) included the integration of sociocultural values (familismo) and environment/burdens (stressors, social determinants, immigrant status) into the intervention content, and more in-App guidance/instruction to facilitate navigation for low health and digital literacy. Interpretation: We produced a digital therapeutic for insomnia for Hispanic adults across the digital literacy spectrum with high acceptability, usability, and potential to confer clinical benefits. Funding: This project was supported by AHRQ HS024274 and a Provost Grant from Columbia University.